A facile approach to synthesize a "star-like" material based on β-cyclodextrin for enhancing the flowability of paraffinic oils. Issue 7 (2nd July 2016) - Wei, Bing; Li, Hao; Xue, Yan
ABSTRACT: A novel compound, which exhibits " star-like " architecture and is expected to be a promising flow improver for paraffinic oils, was presented in the current work. This material was facilely synthesized based on β-cyclodextrin molecule via a catalytic esterification procedure under mild experiment conditions. The chemical formation was characterized by FT-IR, 1 H-NMR, and elemental analysis, respectively. The experimental data revealed that each β-cyclodextrin was attached by approximately seven C14 chains. This type of architecture is supposed to be appropriate to co-crystallize with paraffin melocules through taking the place of a paraffin in crystal lattic and thus disperse the agglomeration of wax crystals. This hypothesis was verified through a yield stress test and rheological analysis. It was observed that after treatment with this compound, the paraffinic oil yielded at a much lower stress value compared to the untreated oil. Moreover, a significant shift of the apparent viscosity vs. temperature curve to the left field occurred. These results demonstrated the capacity of this synthesized compound in enhancing the flowability of paraffinic oils.